REDESAIN RUANG TUNGGU PENUMPANG BUS TRANS KOTA BATAM : STUDI TEKNIS EVALUASI LAYANAN TRANSPORTASI PUBLIK KOTA BATAM - Adi Nugroho; Delia Meldra (JURNAL REKAYASA SISTEM INDUSTRI, 2017)
Ministry of Transportation’s regulation no. 10/2011 defines that every public service, including public transportation, need to meet the minimum standard of service set by the government. It means that it has to qualify on criterias such as regularity, equality, accessability, comfort, safety and security. This research aims to find out the feasible design of Batam Trans Bus stop that fit the criterias.To achieve the goal, this research use qualitative technique, to gain th e information about service performance and sort the users need, and quantitative technique to draw the conclusions. This research also use Qualify Function Deployment (QFD) and Anthropometri. After the observation and measurement analysison some of bus stop in Batam , as example bus stop at Kepri Mall, Batamindo and kavling Baru, it had been found that facilities at Batam Trans Bus Stop haven’t met the minimum standard defines by regulation no.10/2011. Benches, stairs, pavilions, roofs, are facilities that are needed to be upgraded based on user of bus stop. The size differences on facilities are also being the users concern, such as benches height and width, stairs height and doors size.